The role of transition metal ions in hydrogen bonded networks: A density functional molecular orbital theory study - McGrady, J; Mingos, D (1996)
The capacity of biureto- (C2N3O2H 32-) and dithiobiureto- (C2N3S 2H41-) complexes of nickel, L2Ni(bt) and L2Ni(dbt) [L2 = (CO)2, (PH 3)2, (NH3)2, acac -,† (Cl-)2, (CN-) 2] to form hydrogen bonds with complementary probe molecules has been studied using density functional molecular orbital theory. The charge on the trans ligands, L, is found to be the dominant factor in determining the strength of the hydrogen bonding. The π donor and acceptor properties of the ligands are relatively unimportant. Increasing the negative charge on the ligands enhances hydrogen bonding in biureto complexes, where there is an excess of proton acceptor groups. In dithiobiureto complexes, where proton donor groups are in excess, the influence of the trans ligands is much smaller, and in the opposite direction; greater negative charge reducing the strength of the hydrogen bonds. These results suggest an approximately two-fold greater susceptibility of the proton acceptor groups to changes at the metal centre.